Integrasi Peran Sosial dan Akademik H. Muhammad Basuni Imran dalam Pengembangan Pendidikan Islam dan Pemberdayaan Masyarakat - Mas’adah; Mahrus, Erwin; Sumin (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the integration of the social and academic roles of H. Muhammad Basuni Imran in the development of Islamic education and community empowerment. As one of the most influential scholars in West Kalimantan, Basuni Imran made significant contributions to advancing Islamic education and shaping the socio-religious character of the Sambas community. This research employs a qualitative method with a historical approach through the examination of archives, documents, his published works, and relevant supporting literature. The findings indicate that Basuni Imran successfully integrated these two strategic roles in a harmonious manner. As an academic and Islamic thinker, he promoted curriculum reform, strengthened scholarly traditions, and emphasized the balance between rational knowledge and spiritual values. In his social role, he actively nurtured religious life, reinforced social solidarity (ukhuwah), and mobilized community initiatives grounded in Islamic values. The synergy between these dual roles positions Basuni Imran as a transformational scholar who contributed not only to intellectual development but also to the moral, cultural, and socio-economic empowerment of the community.